2022
DOI: 10.3390/ijms23084166
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Tumor Microenvironment in Glial Neoplasm: From Understanding Pathogenesis to Future Therapeutic Perspectives

Abstract: Despite the multidisciplinary management in the treatment of glioblastomas, the average survival of GBM patients is still 15 months. In recent years, molecular biomarkers have gained more and more importance both in the diagnosis and therapy of glial tumors. At the same time, it has become clear that non neoplastic cells, which constitute about 30% of glioma mass, dramatically influence tumor growth, spread, and recurrence. This is the main reason why, in recent years, scientific research has been focused on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Compared to LUAD patients with metastasis or recurrence, early diagnosis and treatment usually result in a prosperous prognosis. A superior biomarker supplies precise guidance and potential value for malignant tumor processing [34]. Through using comprehensive bioinformatics analysis on expression pro le and clinical prognosis, our research revealed that HMGB3 had signi cant diagnostic and therapeutic value on LUAD.…”
Section: Discussionmentioning
confidence: 87%
“…Compared to LUAD patients with metastasis or recurrence, early diagnosis and treatment usually result in a prosperous prognosis. A superior biomarker supplies precise guidance and potential value for malignant tumor processing [34]. Through using comprehensive bioinformatics analysis on expression pro le and clinical prognosis, our research revealed that HMGB3 had signi cant diagnostic and therapeutic value on LUAD.…”
Section: Discussionmentioning
confidence: 87%
“…The tumor microenvironment, which comprises ostensibly normal cells (except heterogeneous cancer cells), including stromal and immune cells, is presumed to be genetically stable and less affected by tumor heterogeneity and has a crucial impact on GBM subtype, recurrence, drug resistance, and, subsequently, the survival of patients; 18 it is acknowledged that these nontumoral cells drastically impact tumor development and progression. 4 Thus, the most promising potential for a therapeutic breakthrough lies in pathways targeting the tumor microenvironment of GBM, since therapeutic regimens that target gliomagenesis pathways are inhibited due to the heterogeneity of the tumor. 3 Moreover, we performed further analyses of the potential mechanisms to investigate the functions of NOD1 in the GBM microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated microglia and macrophages, covering the largest proportion of infiltrating immune cells, are associated with more aggressive phenotypes of GBM. 4 In contrast, NK cells recognize target cells and directly lyse tumor cells but cover the lowest part of all GBM immune infiltrations. 34 The ESTIMATE algorithm revealed a positive link between stromal/immune infiltrations and NOD1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Glioma-associated microglia and macrophages (GAM) are the most abundant population of immune cells, constituting up to 30% of the tumor mass. [21][22][23] Despite the high content of glioma-associated microglia and macrophages (GAM), GBM is considered immunologically "cold" due to relatively poor infiltration of activated T cells and anergic state of those present in TME. 24 Moreover, the broad range of cell-to-cell interactions between cancer cells and components of the TME affects the biological status of the tumor with an increase in its evasion capacity and resistance to treatment.…”
Section: Introductionmentioning
confidence: 99%